O que acontecerá com o modelo alemão? Engajando fontes de diversidade ao nível da empresa dentro da economia alemã - Stefan Kirchner (Estudos de Sociologia)
Traditionally, Germany’s economy has been characterized by a specific model. Currently, transformations and empirical investigations of firm-level diversity challenge this traditional German model. This article summarizes important challenges by discussing four distinct sources of diversity in Germany’s economy: transformations of the institutional framework; key firm-level sources of diversity in Germany’s economy; SMEs (small and medium-sized enterprises) as a forgotten pillar of German capitalism; and the East German path in the German model. Overall, the article argues that the traditional German model has been substantially transformed. Additionally, considering the manifold sources of diversity in Germany’s economy, I call for a theoretical and empirical appreciation of this diversity at the firm level. In doing so the research on the German economy could be substantially advanced and a more accurate picture of the current German model could be drawn.